An Official American Thoracic Society/European Respiratory Society Statement: Key Concepts and Advances in Pulmonary Rehabilitation - Spruit, M.; Singh, S.; Garvey, C.; ZuWallack, R.; Nici, L.; Rochester, C.; Hill, Kylie; Holland, A.; Lareau, S.; Man, W.; Pitta, F.; Sewell, L.; et al. (Stanford University, 2013)
Background: Pulmonary rehabilitation is recognized as a core component of the management of individuals with chronic respiratory disease. Since the 2006 American Thoracic Society (ATS)/European Respiratory Society (ERS) Statement on Pulmonary Rehabilitation, there has been considerable growth in our knowledge of its efficacy and scope. Purpose: The purpose of this Statement is to update the 2006 document, including a new definition of pulmonary rehabilitation and highlighting key concepts and major advances in the field. Methods: A multidisciplinary committee of experts representing the ATS Pulmonary Rehabilitation Assembly and the ERS Scientific Group 01.02, “Rehabilitation and Chronic Care,” determined the overall scope of this update through group consensus. Focused literature reviews in key topic areas were conducted by committee members with relevant clinicaland scientific expertise.The final content of this Statement was agreed on by all members. Results: An updated definition of pulmonary rehabilitation is proposed. New data are presented on the science and application of pulmonary rehabilitation, including its effectiveness in acutely ill individuals with chronic obstructive pulmonary disease, and in individuals with other chronic respiratory diseases.The important role of pulmonary rehabilitation in chronic disease management is highlighted. In addition, the role of health behavior change in optimizing and maintaining benefits is discussed. Conclusions: The considerable growth in the science and application of pulmonary rehabilitation since 2006 adds further support for its efficacy in a wide range of individuals with chronic respiratory disease.